GE_GERICHTE P/15010/2020 vom 6. Mai 2022 - GE Cour de justice (2022)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;ESCROQUERIE;CHANTAGE;FAUX MATÉRIEL DANS LES TITRES | CPP.310.al1.leta; CPP.310.al1.letb; CP.31; CP.156; CP.146; CP.251